Overview of Sample Preparation and Chromatographic Methods to Analysis Pharmaceutical Active Compounds in Waters Matrices - Cristina M. M. Almeida (Separations, 2021)
In the environment, pharmaceutical residues are a field of particular interest due to the adverse effects to either human health or aquatic and soil environment. Because of the diversity of these compounds, at least 3000 substances were identified and categorized into 49 different therapeutic classes, and several actions are urgently required at multiple steps, the main ones: (i) occurrence studies of pharmaceutical active compounds (PhACs) in the water cycle; (ii) the analysis of the potential impact of their introduction into the aquatic environment; (iii) the removal/degradation of the pharmaceutical compounds; and, (iv) the development of more sensible and selective analytical methods to their monitorization. This review aims to present the current state-of-the-art sample preparation methods and chromatographic analysis applied to the study of PhACs in water matrices by pinpointing their advantages and drawbacks. Because it is almost impossible to be comprehensive in all PhACs, instruments, extraction techniques, and applications, this overview focuses on works that were published in the last ten years, mainly those applicable to water matrices.